Análisis de la gestión logística en la empresa Af Boullosa de la ciudad de Iquitos, periodo 2023 - Tafur Ampuero, Joseomar (2024)
Logistics management includes the implementation for the articulation of a series of actions and procedures that are developed and that are mainly focused on ensuring that the products that the company produces or markets arrive in a timely manner at their final destination. The title of the research is “Analysis of logistics management in the AF Boullosa company in the city of Iquitos, period 2023”, and aims to determine the level of logistics management. Their study followed a quantitative type with a descriptive correlational design, making it necessary to use the survey and the questionnaire as a technique and instrument respectively, which was applied to a sample of 23 individuals. The results reveal that the level of logistics management in the company is good, that is, high, due to the average achieved, which was 70% in effectiveness.